2017
DOI: 10.1371/journal.pone.0173230
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and tea consumption are associated with asymptomatic erosive esophagitis in Taiwanese men

Abstract: ObjectiveAsymptomatic erosive esophagitis (AEE) is commonly found in men, and might be a risk factor of developing esophageal adenocarcinoma. We aimed to determine if specific dietary habits increase the risk of AEE in asymptomatic Taiwanese men.MethodsWe recruited male adults undergoing upper gastrointestinal endoscopy for health check. We excluded subjects with reflux symptoms, or taking anti-reflux medications or drugs that potentially impair lower esophageal sphincter function or cause mucosal injury. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 70 publications
3
25
2
Order By: Relevance
“…They found that the risk of asymptomatic erosive esophagitis was greater in those drinking tea than nondrinkers. [13] Another study performed by Filiberti et al [12] suggested that tea consumption could be protective factor for Barrett's esophagus or esophagitis. However, this is a case–control study based on limited subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the risk of asymptomatic erosive esophagitis was greater in those drinking tea than nondrinkers. [13] Another study performed by Filiberti et al [12] suggested that tea consumption could be protective factor for Barrett's esophagus or esophagitis. However, this is a case–control study based on limited subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[8] In observational studies, some case–control studies have reported that there is no correlation between GERD and tea consumption, [9,10] while other studies suggested a positive association between tea drinking and the risk of GERD. [1113] Thus, the effect of tea drinking on GERD risk is still controversial. The aim of this study is to perform a meta-analysis on the relationship between tea drinking and the incidence of GERD.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems that any possible relationship between coffee and GERD may not be obvious in this study. In terms of tea consumption and GERD, several epidemiological surveys had regarded tea as a risk factor of GERD [ 27 , 32 ], although, this relationship varied depending on the type of tea consumed, such as green tea, strong tea or peppermint tea [ 27 , 33 , 34 ], as well as quantity of tea intake [ 32 ]. In this study, no significant association was found between the timing of tea intake and risk of GERD, which is in line with the finding of previous epidemiological reports [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drinking two cups of tea per day was a risk factor for GERD in Syrian undergraduate and graduate students [ 16 ]. Similarly, a study on men from Taiwan found that drinking tea ≥ 4 days a week was associated with asymptomatic erosive esophagitis [ 30 ]. Students with GERD symptoms could be advised to observe if tea or coffee exacerbate their symptoms so that their intake can be limited.…”
Section: Main Textmentioning
confidence: 99%